MRI Findings and Outcome in Molybdenum Cofactor Deficiency - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at Great Ormond Street Hospital, London, UK examined the clinical, brain MRI, biochemical, genetic, and EEG features and outcome in 8 children with a diagnosis of molybdenum cofactor deficiency seen over a 10-year period.